THE EFFECT OF LEARNING DISCIPLINE ON MATHEMATICS LEARNING OUTCOMES - Utama, Ilham Tresna; Sukmanasa, Elly; Wijaya, Ade (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The purpose of this study is to find outThe Effect of Learning Discipline on Mathematics Learning Outcomes. The population in this study were students of fourth grade of SDN 01Gunung Picung. The analysis prerequisite testing technique is in the form of a normality test, then the homogeneity test is carried out. Data that is declared normal and homogeneous is used to test the hypothesis which results show that there isThe Effect of Learning Discipline on Mathematics Learning Outcomes. Simple correlation regression analysis technique produces a relationship model which is expressed in the form of a regression equation, namelyÅ¶ = 88.1 + 1.37X. The results of this study are indicated by statistical analysis which produces a correlation coefficient (rxy) of 0.57. While the coefficient of determination is 32.49%. Regression analysis techniques and simple correlation of learning discipline with mathematics learning outcomes produce an effect which is expressed in the form of a regression equation, namely Å¶ = 88.1 + 1.37X. which means that each increase in learning discipline units causes an increase in mathematics learning outcomes by 0.57 units. Based on the results of the research above, it can be concluded that there is a positive influence between the learning discipline and mathematics learning outcomes on the fourth grade of SDN 01 Gunung Picung, Bogor Regency, 2020/2021 academic year